Answer:
Applying Quotient and power rule. Graphically, for x>0 both curves coincide.
Explanation:
1) Firstly, by applying the Quotient and then the Power Rule, we have a subtraction of the argument and, finally the exponent turns to be the coefficient. As it follows:
![lnx=log_(e)x\\\\f(x) = ln({(x^(2))/(4)})\Rightarrow f(x)=ln{x^2}-ln4\Rightarrow f(x)=2lnx-ln4\\g(x) = 2 ln x - ln 4](https://img.qammunity.org/2021/formulas/mathematics/college/wwiodely1zlbch0wa8kp4hzujzql53nnz5.png)
2) Check the graph below to see this equivalence. to see x>0 they both coincide.